Samoa : Request for Disbursement Under the Rapid Credit Facility-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Samoa. (IMF Staff Country Reports; Country Report ;, 2013)
Samoa was hit hard by a strong tropical cyclone, and the authorities are to be commended for their swift response to the resulting disaster. Economic growth this fiscal year is expected to be significantly lower than projected prior to the cyclone, but there are encouraging signs of early recovery. The need is to aim the fiscal strategy at securing sufficient resources while minimizing borrowing. With subdued inflationary pressures and the need to support the recovery, monetary policy should remain accommodative.